ANALISIS SISTEM PENGOLAHAN ABSENSI KARYAWAN PADA PT. BAKRIE SUMATERA PLANTATIONS TBK BUNUT - Muhammad Yasin Simargolang; Wiyoga Agung Warsito ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - The development of information technology from year to year is increasingly becoming a serious challenge for users of information technology itself and encourages every sector of the organization both formal and informal or other institutions to be able to use it as a support for work activities so that it can produce information that is fast, precise and accurate. PT. Bakrie Sumatera Plantations Tbk Bunut as a company in the field of palm oil and rubber processing certainly requires good management in managing employee attendance data which will later have a positive impact on the development of the company itself. So information is needed that is efficient in maintaining its existence in order to exist and be known by the wider community. One effort to support this is a good computer system. To get a good system, research on the existing system is done. The next step is to do an analysis to find out the strengths and weaknesses of the system. Then the system design is done, namely Flowmap, Data Flow Diagrams, and Context Diagrams. And the last stage is the implementation that changes the design into the programming language stage. Keywords - System, Analysis, Attendance